Shot in the dark [nuclear weapon testing]. - Svoboda, E. (IEEE spectrum)
This paper discusses the future of the National Ignition Facility (NIF) located in Livermore, CA, amid criticisms about whether it can achieve its stated scientific goals and whether such a money-draining project was really necessary in the first place. Envisioned as an ideal site for nuclear weapons testing, the NIF could produce fusion in controlled conditions that would allow weapons specialists to simulate the detonation of different types of bombs to help them assess the status of aging atomic stockpiles without conducting risky test explosions that international law is trying to ban. A major source of concern among critics is the question of whether a fusion reaction that occurs inside a capsule smaller than a fingernail can provide an accurate indication of how a full-size nuclear weapon would detonate. NIF scientists are confident, however, that applying computer-generated formulas to their experimental data can account for such scale differences.